Pembacaan Jarak dan Kecepatan dengan ArUco Marker pada Sistem Koper Follow Me Beroda - Triwahyudin, Agus; Safitri, Hari Kurnia; Fauziyah, Mila (Majalah Ilmiah Teknologi Elektro; Vol 21 No 1 (2022): (Januari - Juni) Majalah Ilmiah Teknologi Elektro, 2022)
The Wheeled Follow Me Suitcase is an automatic robot that can follow human journeys to carry goods to meet their needs. This suitcase has 2 modes; manual and automatic modes. The manual mode of the suitcase will be used like a suitcase in general. While the automatic mode, the suitcase will always follow the owner who already has a special mark (markers). The main components of this system are raspberry pi camera, raspberry pi 4, push button, buzzer, motor driver and dc motor. By doing image processing on special marks (markers) so as to produce a variable distance. The results of processing the reading of the distance variable will be processed into a speed variable, so that the error data range will be obtained. The use of markers of the ArUcoMarker type, limits the distance for reading special marks to a maximum distance of 2 meters which is as stable as possible at a distance of 1 meter. To anticipate failure in reading, a buzzer is used as a sign that the follow me suitcase has been far from the user. In the test results using markers of the ArUco Markers type, a minimum distance of 74 mm is produced, a maximum of 2170 mm. With the smallest reading error rate at a distance of 400 mm and 1100 mm while the largest reading error at a distance of 2000 mm and for the average distance reading error of 0.55%.